2016
DOI: 10.1038/srep38895
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on Cardiac Arrhythmia Ablation Using High-Energy Heavy Ion Beams

Abstract: High-energy ion beams are successfully used in cancer therapy and precisely deliver high doses of ionizing radiation to small deep-seated target volumes. A similar noninvasive treatment modality for cardiac arrhythmias was tested here. This study used high-energy carbon ions for ablation of cardiac tissue in pigs. Doses of 25, 40, and 55 Gy were applied in forced-breath-hold to the atrioventricular junction, left atrial pulmonary vein junction, and freewall left ventricle of intact animals. Procedural success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 52 publications
(56 reference statements)
9
118
0
2
Order By: Relevance
“…In the most recent report of high-energy carbon ions (40-55 Gy) for ablation of cardiac tissue in pigs, no damage of the esophagus, trachea, phrenic nerves, or coronary arteries was observed during 6 months of follow-up. 30 In our previous study on the dose-dependent efficacy of the carbon ion beam, administration of ࣙ10 Gy to the rabbit heart increased Cx43 levels. 6 The administration of 15 Gy did not adversely affect the beagles' general health, induce novel arrhythmias, or cause cardiac malignancies, as observed at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 91%
“…In the most recent report of high-energy carbon ions (40-55 Gy) for ablation of cardiac tissue in pigs, no damage of the esophagus, trachea, phrenic nerves, or coronary arteries was observed during 6 months of follow-up. 30 In our previous study on the dose-dependent efficacy of the carbon ion beam, administration of ࣙ10 Gy to the rabbit heart increased Cx43 levels. 6 The administration of 15 Gy did not adversely affect the beagles' general health, induce novel arrhythmias, or cause cardiac malignancies, as observed at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 91%
“…This therapy has resulted in late myocardial fibrosis and electrically inert tissue without evidence of acute or subacute injury to nearby tissues during 6 months of follow-up. 8,9 Clinical case reports have shown the feasibility of the use of SBRT for this purpose. 10,11 …”
mentioning
confidence: 99%
“…23 SBRT has the potential to overcome these challenges. 8,9 In this case series, we combined noninvasive mapping (electrocardiographic imaging) and noninvasive ablation (SBRT) to treat patients with refractory ventricular tachycardia.…”
mentioning
confidence: 99%
“…This modality was investigated in an animal study and showed a dose-dependent reduction in voltage on mapping and the presence of fibrosis and hemorrhage on histology at treated sites, respectively. 83 In another study, photon beams successfully ablated the atrioventricular node in pigs. However, while the coronary arteries remained intact, there was apoptosis at the sites of myocardial beam entry.…”
Section: Novel Ablation Modalities On the Horizonmentioning
confidence: 98%